Injury-related fatalities in selected governorates of Iraq from 2010 to 2013: Prospective surveillance - Bilukha, Oleg O. (Am J Disaster Med, 2016)
OBJECTIVE: After several years of relative stability in Iraq, the emergence of the Islamic State militant group has spurred a resurgence of violence. This study explores the impact of the conflict on the overall injury profile to estimate the proportion of injury fatalities related to conflict and better understand how violence has affected nonconflict-related injuries. DESIGN: Routine prospective injury surveillance operated by the Iraqi Ministry of Health. SETTING: Surveillance data were collected from coroner offices in eight pilot governorates: Al-Anbar, Baghdad, Basrah, Erbil, Kerbala, Maysan, Ninevah, and Al-Sulaimaniya. PARTICIPANTS: We analyzed all fatalities from external injury causes recorded between January 1, 2010 and December 31, 2013. Analysis included 32,664 fatal injuries. RESULTS: Of all injury fatalities reported, 27.1 percent were conflict-related fatalities, approximately the same proportion as road traffic-related fatalities (24.4 percent) and other unintentional injuries (27.5 percent). The proportion of fatalities from conflict was approximately three times higher among males than females (33.0 percent and 10.3 percent, respectively) and four times higher among adults than children (29.8 percent and 7.3 percent, respectively). The total number of injury fatalities remained stable between 2010 and 2012; an increase in injury fatalities in 2013 was driven primarily by increases in fatalities from both interpersonal violence and conflict. CONCLUSIONS: From 2010 to 2013, nearly one in four injury fatalities in Iraq was attributable to conflict, a notably higher proportion than other conflict-affected countries in the region. The overall profile of nonconflict injuries in Iraq is also distinct from other countries of similar socioeconomic level that have not experienced violence.